BASP1 is a prognostic biomarker associated with immunotherapeutic response in head and neck squamous cell carcinoma - Pan, Xue; Xu, Xun; Wang, Lixuan; Zhang, Siyuan; Chen, Yingyao; Yang, Rongchun; Chen, Xijuan; Cheng, Bin; Xia, Juan; Ren, Xianyue (Frontiers in Oncology, 2023)
Immunotherapy is effective in a subset of head and neck squamous cell carcinoma (HNSCC). However, the unfavorable response rate and inadequate biomarkers for stratifying patients have primarily limited its clinical application. Considering transcriptional factors (TFs) play essential roles in regulating immune activity during HNSCC progression, we comprehensively analyzed the expression alterations of TFs and their prognostic values in HNSCC using TCGA and GEO datasets. Brain abundant membrane attached signal protein 1 (BASP1) was screened out to be upregulated and associated with poor survival in HNSCC patients. BASP1high patients exhibited better response rates to anti-PD-1 immunotherapy and higher expressions of immune checkpoint inhibitors. GO, KEGG and GSEA analyses indicated that the expression of BASP1 was related to several immune-related pathways and immunogenic ferroptosis signature. The infiltration of activated CD8+ T cells was authenticated to be decreased in BASP1high patients using CIBERSORT, EPIC and quanTiseq algorithms. Furthermore, BASP1 was identified to be positively correlated with T cell dysfunction and immune escape in the immune cycle analysis. Moreover, silencing BASP1 triggered ferroptosis in HNSCC cells, representing as increased LDH, lipid peroxidation and ROS levels, and reduced glutathione synthesis. In conclusion, we demonstrated that BASP1 suppressed immunogenic ferroptosis to induce immunosuppressive tumor microenvironment. BASP1 plays a critical role in immune response, and might be a promising classifier for selecting HNSCC patients who benefit from current immunotherapy.